PRODUCTION, HARVEST AND CONSERVATION OF LABLAB PURPUREUS (L) SWEET FORAGE IN SEMI ARID LIVESTOCK REGIONS: THE CASE OF EAST CENTRAL BOTSWANA - Z. Madzonga; K. Mogotsi (Journal of Animal and Plant Sciences, 2014)
In arid and semi arid regions, marked seasonal fluctuations in nutritional quality of natural pastures compromise livestock productivity and necessitates incorporation of leguminous plants as supplements. To establish the extent of Lablab purpureus forage production under extensive livestock systems in Botswana, a survey of randomly selected households was conducted in Central and North East Districts during the 2012/2013 planting season. Farmers were primarily engaged in L. purpureus production to produce hay to supplement their livestock during times of feed scarcity while a few sold it as fodder. The main hay storage techniques employed were (1) small rectangular bales, (2) loose piles/bundles of cured forage and (3) cured and chopped forage packed in bags. Some of the highlighted challenges in harvesting, curing and storage of L. purpureus included leaf loss, inadequate access to baling machinery, hay damage from direct exposure to sun and rain as well as inappropriate storage facilities. Other challenges were related to seed - inadequate supply, poor quality as well as high cost. To counter these challenges, farmers employed several mitigation measures. Because of the growing popularity of L. purpureus among livestock producers, intensified awareness campaigns can accelerate its adoption and thereby alleviate seasonal animal nutritional deficits.
Keywords: curing; forage storage; hay making; leaf shattering; livestock feed; seed quality